Ujemanje med povedkom in osebkom v kopulativnih stavkih - Ribič, Janja (Jezik in slovstvo, 2016)
The article discusses subject-verb agreement in copulative clauses with the following structure: nominal phrase - verb 'to be' - nominal phrase. Subject-verb agreement is not clearly defined in such cases in Slovene. Usage shows that the copula sometimes agrees with the subject complement, but at other times with the subject. There are few theories regarding this linguistic problem, hence the problem remains unresolved. The article briefly discusses the existing theories and attempts to determine an agreement rule based on examples found in the Slovene corpus Gigafida.
Keywords: Slovene; slovenščina; syntax; skladnja; ujemanje; povedek; osebek; povedkovo določilo